Kebutuhan Investasi Sektor Basis Industri Per Kecamatan di Kabupaten Gianyar Dalam Rangka One Village One Product - Putra, Komang Agus Triasta; Aswitari, Luh Putu (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 2, No. 12, Desember 2013 (pp. 547-569), 2013)
Gianyar regency is the centre of micro and mid-micro industry (IKM) in bali which gives a big  contribution toward Product Domestic Regional Bruto (PDRB) and devisa} to gianyar. This research aims to find out the investment needs of  which industrial sector that is considered to be a basic sector industry to determine OVOP from 2013-2016. Data that are used in this research is came from BPS, department of industry and commerce and also relevant agencies. This research used Location Quotient (LQ) and Incremental Capital Outpu RatiotI (ICOR) analysis technique. From this research, it can be known that from each sub district there are 1 to 5 basic sectors and wooden handmade furniture is determined to be a basic sector that is most seen in each sub district of gianyar. The investment needs value from 2013 to 2016 can be estimated from Rp. 47.755.780 billion to Rp. 68.088.251.000 billion which have been distributed to each sub district in gianyar.
Keywords: OVOP; locatiom quotient (LQ); estimation of investment needs value